The psychosocial impact of home use medical devices on the lives of older people: a qualitative study - Thomson, Ross; Martin, Jennifer L.; Sharples, Sarah (BioMed Central, 2013)
Background Increased life expectancy and the accompanying prevalence of chronic conditions have led to the focus and delivery of health care migrating from the hospital and into people’s homes. While previous studies have investigated the integration of particular types of medical devices into the home, it was our intention to describe how medical devices are integrated into the lives of older people. Methods Adopting a qualitative study design, 12 older people, who used medical devices in the home, took part in in-depth, semi structured interviews. In 7 of the interviews participants and their partners were interviewed together. These interviews were recorded, transcribed and analysed thematically. Results Two themes were constructed that describe how medical devices that are used in the home present certain challenges to older people and their partners in how the device is adopted and the personal adaptations that they are required to make. The first theme of 'self-esteem’ highlighted the psychological impact on users. The second theme of 'the social device' illustrated the social impact of these devices on the user and the people around them. Conclusions We found that these devices had both a positive and negative psychosocial impact on users’ lives. An improved understanding of these psychological and social issues may assist both designers of medical devices and the professionals who issue them to better facilitate the integration of medical devices into the homes and lives of older people.